(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Diabetes mellitus is the most prevalent metabolic disorder. Previous related studies have shown that, lungs are target organs in diabetic micro-angiopathy. The present study was designed to investigate the spirometric indices in patients with type 2 diabetes referred to the outpatient clinic of Imam Hussein hospital in Shahroud, Iran. Method: This comparative study included 50 patients with type 2 diabetes and 50 non-diabetic subjects who were matched in terms of weight, age, and sex, and were referred to the Diabetes clinic of Imam Hussein hospital in Shahroud, Iran. MIR SPIROLAB III spirometer was used for spirometric tests to obtain FEV1, FVC, PEFR, and FEF 25-75. Decrease in these indices is determinant of pulmonary complications. Indices were compared between two groups. The relationships between some variables like glycated hemoglobin (HbA1c) and type of their treatment with the severity of spirometric disturbances were also assessed. Result: The average age was equal to 56.3 years old (with SD of 6.3 years) and 58.3 years old (with SD of 6.3 years), respectively in non-diabetic and diabetic group. Comparison of the FEV1, FVC, PEFR, and FEF 25-75 indices between diabetic and non-diabetic groups showed a significant difference (P.V<0.05). No significant difference was found in the FEV1/FVC ratio. According to the Pearson correlation formula, there was a significant association between decreased spirometric indices and increased concentration of Hb A1C (-.630, -.635 and-.374 for FEV1, FVC, and PEFR, respectively). There was no association between decreased concentration of FEV1/FVC and increased HbA1c. Conclusion: The findings of the study revealed that, there was a significant decrease in pulmonary functions in the diabetic group. Impaired pulmonary function can be detected in early stages of diabetes and studying the pulmonary function can be easily preformed. Accordingly, screening lungs function should be carried out regularly, as well as integrating in other routine examinations and screening tests.